Micro/Nano Devices for Blood Analysis, Volume II - Lima, Rui A.; Minas, Graça; Catarino, Susana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The development of micro- and nanodevices for blood analysis continues to be a growing interdisciplinary subject that demands the careful integration of different research fields. Following the success of the book "Micro/Nano Devices for Blood Analysis", we invited more authors from the scientific community to participate in and submit their research for a second volume. Researchers from different areas and backgrounds cooperated actively and submitted high-quality research, focusing on the latest advances and challenges in micro- and nanodevices for diagnostics and blood analysis; micro- and nanofluidics; technologies for flow visualization and diagnosis; biochips, organ-on-a-chip and lab-on-a-chip devices; and their applications to research and industry.